Aircraft fuel system prognostics and health management - Wang, Xiaoyang (Cranfield University, 2012)
This thesis contains the specific description of Group Design Project (GDP) and Individual Research Project (IRP) that are undertaken by the author and form part of the degree of Master of Science. The target of GDP is to develop a novel and unique commercial flying wing aircraft titled FW-11. FW-11 is a three-year collaborative civil aircraft project between Aviation Industry Corporation of China (AVIC) and Cranfield University. According to the market analysis result conducted by the author, 250 seats capacity and 7500 nautical miles were chosen as the design targets. The IRP is the further study of GDP, which is to enhance the competitive capability by deploying prognostics and health management (PHM) technology to the fuel system of FW-11. As a novel and brand-new technology, PHM enables the real-time transformation of system status data into alert and maintenance information during all ground or flight operating phases to improve the aircraft reliability and operating costs. Aircraft fuel system has a great impact on flight safety. Therefore, the development of fuel system PHM concept is necessary. This thesis began with an investigation of PHM, then a safety and reliability analysis of fuel system was conducted by using FHA, FMEA and FTA. According to these analyses, fuel temperature diagnosis and prognosis were chosen as a case study to improve the reliability and safety of FW-11. The PHM architecture of fuel temperature had been established. A fuel temperature prediction model was also introduced in this thesis.
Keywords: PHM; Reliability; Safety; Fuel temperature prediction; Flying wing